Generation of a Single-Domain Antibody against Isolated Escherichia Coli that Causes Camel-Calf Death - Faysal Abdishakur Hassan; Abdelhaq Anouassi; Kanyarat Thueng-in; Mariena Ketudat-Cairns; Rangsun Parnpai (Journal of Veterinary Healthcare, 2021)
Antibodies and antibody fragments, especially single-domain antibodies known as nanobodies, are important tools in diagnostics, research, and therapeutics. In a conventional antibody, light and heavy chains contribute to the formation of the antigen binding site. In addition to conventional antibodies, old and new world camels also have heavy-chain antibodies (hcAbs), which lack the light-chain antibodies that usually bind to the antigen, as well as single domain antibodies, the VHH domain, which are the smallest antigen-binding fragments and have high solubility, stability, and specificity. A VHH library against E. coli lipopolysaccharide (LPS) was produced using the camel immune system. E. coli strains from dead camel calves were isolated to extract the LPS and used to immunize a 2-year-old female camel. After isolating mononuclear lymphocytes for RNA extraction and amplification of the VHH gene, the PCR product was cloned into the pF1AT7 Flexi vector and transformed into JM109 E. coli competent cells by heat shock, resulting in a comprehensive VHHs library with 6.9 × 104 cfu/µg. The VHHs were expressed and screened with ELISA and PCR. Eleven colonies were positive by PCR, six of which were sequenced and submitted to Genbank compared with GenBank data to confirm the production of nanobodies with a similarity >90%.
Keywords: veterinary